SOCIALIZATION OF THE USE AND MANUFACTURE OF HAND SANITIZERS IN ANTICIPATING THE IMPACT OF CORONA VIRUS DISEASE (COVID-19) - Tengku Putri Lindung Bulan; Yusnawati Yusnawati; Mauliza Mauliza (LPPM dan PM Universitas Samudra, 2021)
The Covid-19 virus first appeared in 2019. The World Health Organization (WHO) has declared the corona virus a pandemic. This has made the government and the world community more aware of the spread of the corona virus. Although it is important to find reliable information, we also need to know the steps to fortify ourselves from stress and excessive panic amid the corona outbreak. The government urges every community to carry out independent isolation and reduce activities outside the home. In addition, the government also calls on implementing a clean lifestyle to prevent the transmission of Covid-19. One of them is to keep your hands clean. The difficulty of getting hand sanitizers nowadays makes people worry about having to do activities outside the home. In accordance with the analysis, the